A metal–organic framework derived electrical insulating–conductive double-layer configuration for stable lithium metal anodes. Issue 23 (4th June 2021) - Man, Jianzong; Liu, Wenlong; Zhang, Haibang; Liu, Kun; Cui, Yongfu; Yin, Jinpeng; Wang, Xinyu; Sun, Juncai
Abstract : An electrical insulating–conductive double-layer configuration is designed to simultaneously realize low volume expansion and dendrite-free lithium metal anodes. Abstract : Controlling lithium dendrites growth and alleviating the volume expansion of lithium metal anodes are two key factors to develop high energy density lithium metal batteries. In this work, a planar Cu collector was modified by coating carbonized ZIF-67 as the bottom layer and ZIF-67 as the top layer to form an insulating–conductive double-layer configuration of the electrode (denoted as ICDL/Cu). Due to the insulating properties and high specific surface area of ZIF-67, lithium can be homogeneously deposited on the bottom layer through the top layer. The bottom layer carbonized ZIF-67 with lithiophilic Co nanoparticles and porous polyhedron are conducive to homogeneous deposition of lithium with reduced local current density. Such a porous structure ensures a low volume expansion during the lithium plating/stripping process. The symmetrical cell of ICDL/Cu–Li achieves a long cycling lifetime (more than 1100 h) with a low voltage hysteresis (11 mV) at 1 mA cm −2 for a plating/stripping capacity of 1 mA h cm −2 . As a proof of concept, full cells based on ICDL/Cu–Li‖LiFePO4 deliver excellent rate performance and cycling stability compared with the bare Li‖LiFePO4 one, indicating that the unique ICDL configuration is promising for practical applications.